PERANCANGAN APLIKASI PEMESANAN OBAT SECARA ONLINE BERBASIS ANDROID MENGGUNAKAN METODE PROTOTYPE (STUDI KASUS : APOTEK NAILA RAJA) - Rasyid Dwi Saputra; Ardianto Moenir (CV. Multi Kreasi Media, 2023)
Naila Raja Pharmacy is a company engaged in the sale of prescription or non-prescription drugs and now the company is still using a manual system for sales or data processing. On systems that use manuals such as using Microsoft Excel and stationery. So that the company needs an information system that can later help the company in sales or data management that can overcome if there are obstacles. To overcome this problem, the author uses the Prototype model in making reports. It is hoped that by using this prototype model, employees can make reports systematically and quickly. So that by applying the Prototype model it can help and facilitate employees in making their reports. In this implementation, the application uses the PHP programming language and stores the data using MySQL. Based on the results of the Prototype model analysis, it can be concluded that the reporting process becomes more effective and faster, thus making employees quickly make reports. Researchers have also provided an Android-based application program to make it easier for customers to order drugs online and make it easier for employees to make reports systematically.